2007
DOI: 10.1037/0735-7028.38.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of providing mental health services in Spanish.

Abstract: The disparity in mental health services to Spanish-speaking clients is well documented. This study examines the service delivery experiences of Spanish-speaking mental health providers by exploring their perceptions and concerns regarding their competence and training to provide services in Spanish. It also identifies practitioner priorities for improving training experiences specific to bilingual mental health service delivery. Implications for graduate psychology programs are discussed in an effort to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 29 publications
7
85
0
2
Order By: Relevance
“…Similar to the findings reported by Castaño et al (2007), all participants in this study reported that they had not received any kind of formal training in providing counseling services in another language. These findings support those of other researchers (Biever et al, 2002;Verdinelli & Biever, 2009) who stated that even though there are bilingual counselors possibly capable of providing services to LEP clients, these counselors may be hesitant to do so because of a lack of training.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar to the findings reported by Castaño et al (2007), all participants in this study reported that they had not received any kind of formal training in providing counseling services in another language. These findings support those of other researchers (Biever et al, 2002;Verdinelli & Biever, 2009) who stated that even though there are bilingual counselors possibly capable of providing services to LEP clients, these counselors may be hesitant to do so because of a lack of training.…”
Section: Discussionsupporting
confidence: 77%
“…Mental health counselors-intraining speaking a second language often employed informal resources of double-checking their language skills with classmates, family members, or friends. Few reported utilizing the informal training discussed by Castaño et al (2007) (e.g., popular media, books, journals, immersion). Five of the six participants identified the connection with the client as one of the most positive consequences of doing bilingual counseling, attributing it to being perceived as having the language skills as well as the understanding of cultural values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nous ne pouvons pas tenir pour acquis qu'une personne bilingue pouvant converser dans une langue seconde peut s'exprimer au même niveau qu'une personne dont cette langue est la première langue. Cet enjeu s'avère encore plus marqué quand le client est en détresse, exprime des émotions, ou analyse et interprète des événements (Castano, Biever, Gonzalez et Anderson, 2007).…”
Section: Importance De La Langue Dans La Distribution De Services Socunclassified
“…Ainsi, appuyé par toute une équipe de collaborateurs chevronnés, le CNFS a lancé en janvier 2012 une première série de matériel imprimé (Bouchard et Savoie, 2011;Lortie, Lalonde et Bouchard, 2012) (Castaño, et collab., 2007) démontre également que certains facteurs, tels la douleur, la vulnérabilité ou le stress, font souvent en sorte que les personnes, qui maîtrisent pourtant bien le français et l'anglais dans d'autres circonstances, n'arrivent plus à s'exprimer adéquatement dans leur langue seconde. D'ailleurs, selon Sarah Bowen (2001), les barrières linguistiques engendrent des risques tant pour ces personnes que pour l'organisme qui leur offre des soins ou des services.…”
Section: La Mise En Contexteunclassified